Transcriptomic analysis of the effects exerted by curcumin on dihydrotestosterone-induced ovarian granulosa cells - Chen, Dejian; Yu, Qian; Sheng, Shuhao; Cai, Lingshi; Zheng, Jisuo; Zhang, Yaling (Frontiers in Endocrinology, 2025)
PurposeHyperandrogenism is a leading cause of developmental retardation in ovarian granulosa cells. Previous studies have indicated that curcumin significantly improves follicular dysplasia, a characteristic of the polycystic ovary syndrome. Our purpose was to explore the signaling pathways which enable curcumin to protect the development of hyperandrogen-induced granulosa cells.MethodsOvarian granulosa cells treated with or without curcumin at different dihydrotestosterone (DHT) levels, were screened for cell viability, reactive oxygen species production, and apoptosis. RNA sequencing (transcriptome sequencing) was used to determine global gene expression in DHT-induced granulosa cells treated with curcumin.Results24 hours of combined curcumin and DHT treatment inhibited granulosa cell viability in a dose-dependent manner. Curcumin upregulated estrogen synthesis-related enzymes, downregulated lipid metabolism-related genes and the glucuronic acid process, inhibited androgen receptor (AR) activity, significantly improved cell viability, and corrected granulosa cell development. Gene set enrichment and genome transcriptome pathway analyses revealed the potential role played by curcumin in protecting granulosa cell development.ConclusionHigh androgen levels may disrupt steroid hormone synthesis and lipid metabolism pathways associated with granulosa cell development, thereby activating AR and inhibiting estrogen biosynthesis. Curcumin restores granulosa cell development by correcting abnormal steroid gene expression and disordered lipid fatty acid metabolism.